Crediting Adult Learning - Bruce Spencer; Derek Briton; Winston Gereluk (Adult Education Research Conference, 2000)
This paper reports on the uncertainties and dilemmas experienced by three researchers as they continue to explore how informal and non-formal union-sponsored learning can be translated into college and university credits.